Behavioral addiction as a comorbidity to pathological gambling: Implication for screening and intervention in health setting - Manoj Kumar Sharma; Girish N Rao; Vivek Benegal; K Thennarasu; Divya Thomas (Indian Journal of Social Psychiatry, 2019)
Background: Gambling has been portrayed in many anecdotes in the culture of India as an addiction associated with psychosocial dysfunctions. The present study assessed pathological gambling and other behavioral addictions as a comorbid condition in an urban Indian community. Materials and Methods: A total of 3250 individuals were approached to report on gambling behavior and other behavioral addictions using a door-to-door survey approach and 2755 participated in the study. The Lie–Bet Tool for gambling, Behavioral Addiction Screening Checklist, and Internet Addiction Test were administered. Results: Of those surveyed in the age group of 18–50 years, 1.2% reported pathological gambling along with the presence of eating, mobile phone, or television addiction. Only 0.3% of the participants reported the need to change gambling behaviors. Conclusions: These findings have implications for screening and intervention for the management of behavioral addictions that are comorbid with gambling.